Transporte em um ponto quântico aberto: estudo de autocorrelações da condutância e do emaranhamento - Miranda, Yoshiyuki Sugawara (2017)
The transport of electrons through nanostructures is an important achievement of quantum mechanics. In this dissertation, quantum transport will be explored through the statistic formalism of random scattering matrices, wich will be thoroughly explored in its own chapter. This formalism will then be adequated to be used in computer simulation to achieve some interesting results. We will study Landauer’s formulation for the conductance at low temperatures adapted to scattering matrices. Through this formulation, we will obtain conductance curves, autocorrelation curves, and finally we will analyze the width of the autocorrelation curves for different resonances. We will also study a specific process of generation of entanglement of formation, as defined byWooters, following a model created by Beenakker. Following the same methodology used for the conductance, we will use the scattering matrices formalism to obtain autocorrelation curves for entanglement and conductance. Exclusively for entanglement and concurrence, some new results will be presented through graphs and histograms of probability of entanglement and concurrence for some energies of interest. The results for both the conductance and the entanglement will be obtained through similar systems, consisting of an open quantum dot with two leads and four channels, studied according to the necessity of each formulation.